The carboxy‐terminal segment of the human LINE‐1 ORF2 protein is involved in RNA binding. Issue 1 (21st September 2013) - Piskareva, Olga; Ernst, Christina; Higgins, Niamh; Schmatchenko, Vadim
Abstract : The human LINE‐1/L1 ORF2 protein is a multifunctional enzyme which plays a vital role in the life cycle of the human L1 retrotransposon. The protein consists of an endonuclease domain, followed by a central reverse transcriptase domain and a carboxy‐terminal C‐domain with unknown function. Here, we explore the nucleic acid binding properties of the 180‐amino acid carboxy‐terminal segment (CTS) of the human L1 ORF2p in vitro . In a series of experiments involving gel shift assay, we demonstrate that the CTS of L1 ORF2p binds RNA in non‐sequence‐specific manner. Finally, we report that mutations destroying the putative Zn‐knuckle structure of the protein do not significantly affect the level of RNA binding and discuss the possible functional role of the CTS in L1 retrotransposition. Abstract : The 180‐aa C‐terminal segment (CTS) of human L1 ORF2p was expressed and purified from bacteria. The nucleic acid binding properties of the CTS of L1ORF2p were examined in vitro . The CTS of L1 ORF2p is an RNA binding domain. The CTS of L1 ORF2p binds RNA in non‐sequence‐specific manner in the low nanomolar range. Disruption of the putative Zn‐knuckle structure does not significantly affect RNA binding.